2011
DOI: 10.1016/j.immuni.2011.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Tight Regulation of Memory CD8+ T Cells Limits Their Effectiveness during Sustained High Viral Load

Abstract: Summary To design successful vaccines for chronic diseases, an understanding of memory CD8+ T cell responses to persistent antigen re-stimulation is critical. However, most studies comparing memory and naïve cell responses have only been performed in rapidly cleared acute infections. Herein, by comparing the responses of memory and naïve CD8+ T cells to acute and chronic lymphocytic choriomeningitis virus (LCMV) infection, we show that memory cells dominated over naïve cells and were protective when present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
189
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(214 citation statements)
references
References 57 publications
23
189
2
Order By: Relevance
“…We observed complete protection only when the frequency of memory CD8 ϩ T cells was high. In agreement with our findings, West et al demonstrated that a high frequency (10 5 ) of virus-specific memory CD8 ϩ T cells from P14 transgenic mice were able to rapidly reduce or clear LCMV clone 13 virus (55). Thus, independent of the reason for the inability of ITYRFYLI-and STLNFNNL-pulsed DCs to induce a response, our data suggest that protection strongly correlates with productive immunization and that the immunogenicity of a peptide may vary with the method of immunization.…”
Section: Cd8supporting
confidence: 93%
“…We observed complete protection only when the frequency of memory CD8 ϩ T cells was high. In agreement with our findings, West et al demonstrated that a high frequency (10 5 ) of virus-specific memory CD8 ϩ T cells from P14 transgenic mice were able to rapidly reduce or clear LCMV clone 13 virus (55). Thus, independent of the reason for the inability of ITYRFYLI-and STLNFNNL-pulsed DCs to induce a response, our data suggest that protection strongly correlates with productive immunization and that the immunogenicity of a peptide may vary with the method of immunization.…”
Section: Cd8supporting
confidence: 93%
“…Such observations certainly underscore the challenges associated with the definition of general principles applicable to T cell-mediated immune protection, but it should also be noted that clinically relevant differences (e.g., the level of infectious pathogen) may emerge at times only under very specific experimental conditions (e.g., the "right" combination of transferred CD8 + T M numbers, pathogen challenge dosage, and timing of analyses). Therefore, a combinatorial analysis of such experimental parameters will be particularly informative (52).…”
Section: Discussionmentioning
confidence: 99%
“…Short-term stimulation cultures (5 h) with LCMV-GPand -NP-derived peptides (CD8 ϩ T cell determinants, GP 33 , GP 92 , GP 118 , GP 276 , NP 205 , and NP 396 ; CD4 ϩ T cell determinants, GP 64 and NP 309 ) in the presence of the protein transport inhibitor brefeldin A (BFA) were performed as described previously (39) to evaluate inducible T cell functionalities. Please note that the CD4 ϩ T cell population specific for the I-A b -restricted GP [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] determinant also reacts with longer (GP 61-80 ) and shorter (GP [66][67][68][69][70][71][72][73][74][75][76][77] ) versions of this epitope (37).…”
Section: Micementioning
confidence: 99%